The relationship between organizational factors and information systems success: an empirical investigation in the Malaysian Electronic-Government Agencies - Ramlah Hussein,; Nor Shahriza Abdul Karim,; Mohd Hasan Selamat,; Ali Mamat, (Penerbit UKM, 2007)
Information system success has been widely discussed in the past two decades. As systems and technologies are being improved and developed, discussions on their effectiveness and evaluation on their success have been continuously debated by researchers, scholars and practitioners. Besides the major concern of IS effectiveness, factors influencing IS effectiveness are also important. One of these factors is organizational factor. Using perceptual measures, this study aims to investigate the influence of organizational factors on IS success. Survey questionnaires were gathered from 201 users from four central agencies in Putrajaya, Malaysia. Seven items were identified to influence IS success. They are top management support, decision-making structure, management style, managerial IT knowledge, budgeting method, goal alignment, and resources allocation. The study also identified four IS success dimensions; systems quality, information quality, perceived usefulness, and user satisfaction. The study found that the IS success variables are significantly and highly correlated. The study also found all the organizational factors are significantly correlated to the four IS success factors investigated. Further analyses also found goal alignment as the highest predictor of IS success, followed by management style and centralization. Conclusively, it was clear that the significant relationship between the organizational factors investigated and IS success dimensions evidently indicate the importance of these factors in ensuring successful information systems.